2019
DOI: 10.11144/javeriana.upsy18-2.asbc
|View full text |Cite
|
Sign up to set email alerts
|

Análisis sociobibliométrico comparativo de la carrera de Psicología de la Universidad de Buenos Aires (1996-2017)

Abstract: Con el objetivo de ofrecer datos públicos y empíricos desde una perspectiva sociobibliométrica sobre la formación ofrecida por la Licenciatura en Psicología de la Universidad de Buenos Aires (Argentina), se realizó un análisis cuantitativo y cualitativo de la bibliografía de las 22 asignaturas obligatorias de los ciclos básico y profesional (N = 2 572), de acuerdo a 12 indicadores sociobibliométricos, comparándose los resultados con estudios de décadas anteriores. Los hallazgos indican una predominancia hegemó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Psychology programs at Argentinian universities have highly structured and defined curricula. These programs are mostly composed of highly delimited, stable, and required courses that tend to maintain their contents and staff over the years without significant variations (Fierro et al, 2018).…”
Section: Diverse Traditions: Differences Between Argentinian and International Universitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychology programs at Argentinian universities have highly structured and defined curricula. These programs are mostly composed of highly delimited, stable, and required courses that tend to maintain their contents and staff over the years without significant variations (Fierro et al, 2018).…”
Section: Diverse Traditions: Differences Between Argentinian and International Universitiesmentioning
confidence: 99%
“…Drawing from several regional and international conferences and resolutions (Ardila, 1978;Bickman, 1987;Raimy, 1950) Argentinian psychologists concluded that the evaluation and accreditation of psychology programs was a potential way of addressing some of the main deficits of Argentinian psychology, such as its overdependence on a single theoretical system (psychoanalysis), its dated or anachronistic content and readings, its scarce research activities and outputs, and its exclusive emphasis on applied, professional, and clinical training (Di Doménico & Piacente, 2011;González, 2018). Accreditation standards and parameters were debated and established by Argentinian public and private professional and academic associations between 2004 and 2009 (Fierro, 2018). In September 2009, Argentina's Ministry of Education passed the 343/09 Ministerial Resolution, which approved and adopted the aforementioned standards for the accreditation processes (Ministerio de Educación, 2009).…”
Section: Evaluation and Accreditation Processes In Argentinian Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation